THE ROLE OF INNOVATION IN ENGLISH LANGUAGE LEARNING (Ustozlar uchun, 2026)
In recent decades, innovation has become a central factor in the development of education systems worldwide. English language learning, in particular, has undergone significant transformation due to technological, pedagogical, and methodological innovations. This article explores the role of innovation in English language learning, focusing on digital technologies, innovative teaching methods, and learner-centered approaches. The study analyzes how innovation enhances motivation, improves language skills, and supports autonomous learning. Furthermore, the article discusses challenges related to the implementation of innovative practices and offers recommendations for effective integration of innovation into English language education. The findings suggest that innovation plays a crucial role in improving the quality and effectiveness of English language learning when applied thoughtfully and systematically.